HUMAN RIGHTS BASED LAW ENFORCEMENT FOR THE VIOLATION OF LOCAL REGULATION BY CIVIL SERVICE POLICE OF SEMARANG MUNICIPALITY - Joko Setiyono (Diponegoro Law Review, 2016)
In the era of regional autonomy, the role of civil service police in the enforcement of Local Regulations is crucial to support regional development. However in practice, civil service police often find obstacles and resistance from the public they face. Therefore, it is required for civil service police to act on the base of human rights during the regulation enforcement process. The results hows that the performance of Semarang civil service police in conducting the Local Regulations enforcement process during 2009-2014 had been done based on human rights. There are still any resistance from the public in some actions, but it can be understood as the result of lack of socialization about the regulations, lack of dialogue and coordination with the citizens, as well as lack of satisfaction of citizens in the solution or redress given to them.  Keywords : human rights, enforcement, violation, local regulation, municipality